Region and nation in India - Wallace, Paul, 1931-; Park, Richard Leonard (New Delhi : Oxford & IBH Pub. Co. : American Institute of Indian Studies, 1985)
Commemoration volume honoring Richard L. Park.
Includes bibliographies and index.
Keywords: Park, Richard Leonard; Regionalism -- India; India -- Politics and government